1977
DOI: 10.1037/0021-843x.86.4.389
|View full text |Cite
|
Sign up to set email alerts
|

Motivational and associative aspects of mild depression in skill and chance tasks.

Abstract: In Experiment 1, the levels of aspiration and expectancies for success of mildly depressed and nondepressed college students on a skill and chance task were studied. The two groups did not differ in expectations for success, but the depressed students displayed elevated levels of aspiration, particularly for the skill task. Experiment 2 tested the prediction, based on an attainment discrepancy model, that increases in expectancy for success would be a function of the interaction of performance level and the sk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(19 citation statements)
references
References 25 publications
0
19
0
Order By: Relevance
“…Empirical findings, however, failed to reach a consistent conclusion. Some findings showed supportive evidence (Golin & Terrell, 1977;Hewitt & Flett, 1991a, b), but many did not (Alden, Bieling, & Wallace, 1994;Carver & Ganellen, 1983;Kanfer & Zeiss, 1983;Wright & Mischel, 1982). Qian and Chen (1996) compared depressed and nondepressed people and found that depressed people did not hold excessively high standards in comparison with nondepressed people, whereas they did evaluate themselves as being lower ability than nondepressed subjects.…”
mentioning
confidence: 97%
“…Empirical findings, however, failed to reach a consistent conclusion. Some findings showed supportive evidence (Golin & Terrell, 1977;Hewitt & Flett, 1991a, b), but many did not (Alden, Bieling, & Wallace, 1994;Carver & Ganellen, 1983;Kanfer & Zeiss, 1983;Wright & Mischel, 1982). Qian and Chen (1996) compared depressed and nondepressed people and found that depressed people did not hold excessively high standards in comparison with nondepressed people, whereas they did evaluate themselves as being lower ability than nondepressed subjects.…”
mentioning
confidence: 97%
“…More depressed subjects expressed a greater need to excel in all endeavors to feel worthwhile. Similarly, Golin and Terrell (1977) found that depressed subjects have higher maximum and minimum goals on a test of infonnation than do nondepressed subjects. Finally, some indirect evidence regarding standards has been reported by Biennan (1981), who found that given the same objective level of perfonnance on a social empathy task, nondepressed subjects are significantly more likely to rate their own perfonnance as successful than depressed subjects are.…”
Section: Effects Of Task Outcome and Subjective Standard On State Depmentioning
confidence: 88%
“…SUbjects with high subjective standards expressed significantly more confidence than subjects with low subjective standards. Since Fibel and Hale (1978) have reported that depression in college students is negatively correlated with expectancy for success, whereas Golin and Terrell (1977) have reported no difference between depressed and nondepressed subjects in task expectancy, it appears unlikely that higher levels of self-confidence would be expressed by more depressed subjects. Such a finding would also run counter to studies that have consistently found depressed subjects to be lower in selfesteem (Flippo & Lewinsohn, 1971).…”
Section: Discussionmentioning
confidence: 99%
“…Adults with low self-esteem tend to evaluate their performance negatively, not so much because they have been less successful, but because of the stringent criteria they use for evaluating their performance as successful (Warren, 1976). When the client's level of aspiration is too high, average performance may be deemed a failure (Golin & Terrell, 1977). For example, one client became depressed when his annual salary dropped for the first time in eight years.…”
Section: Help Clients Revise Their Goals and Standardsmentioning
confidence: 98%
“…Excessively high goals may make it difficult for clients to believe they deserve praise or positive reinforcement for their efforts (Golin & Terrell, 1977). Depressed clients often set goals that are unrealistic, unobtainable, overly abstract, vague, or too far into the future (Rehm, 1982).…”
Section: Help Clients Revise Their Goals and Standardsmentioning
confidence: 98%